2010
DOI: 10.15218/zjms.2010.012
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antimicrobial activity of Miswak extracts against some oral pathogenic isolates

Abstract: Background and objective: Siwak, Miswak, or Arak (Salvadora persica ) belongs to Salvadoraceae and is considered as the most widely used twigs since early times by Babylonians some 7000 years ago, it was later used throughout the Greek and Roman empires, and has also been used by ancient Egyptians and Muslims. The aim of this study was to determine the antibacterial activities of different extracts of Siwak on the growth of different oral isolates of Streptococcus mutans, Staphylococcus aerus and Candida albic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…Plant alcoholic extracts were more effective against bacterial growth than aqueous extracts (Tables 2 and 3) which could be due to solubility of chemical constituents. Alkaloids are more soluble in organic solvents such as alcohol than in aqueous solvents (water in present study) therefore the alcohol extracts were more active against microbial growth than aqueous extracts (13,8,3). Agar disc diffusion techniques were shown to be more effective in the determination of plant extract effects than disc saturation methods because in agar disc diffusion technique exact amounts of plant extracts laid on each disc by using a micropipette while in disc saturation techniques, the discs were immersed in beakers which contain the solutions.…”
Section: Groups Of Chemical Compounds Detected In Plant Extractmentioning
confidence: 59%
See 1 more Smart Citation
“…Plant alcoholic extracts were more effective against bacterial growth than aqueous extracts (Tables 2 and 3) which could be due to solubility of chemical constituents. Alkaloids are more soluble in organic solvents such as alcohol than in aqueous solvents (water in present study) therefore the alcohol extracts were more active against microbial growth than aqueous extracts (13,8,3). Agar disc diffusion techniques were shown to be more effective in the determination of plant extract effects than disc saturation methods because in agar disc diffusion technique exact amounts of plant extracts laid on each disc by using a micropipette while in disc saturation techniques, the discs were immersed in beakers which contain the solutions.…”
Section: Groups Of Chemical Compounds Detected In Plant Extractmentioning
confidence: 59%
“…The growing plant is said to repel insects and moles (2). Published literatures in this field had demonstrated the effects of such a plant extracts on fungal and bacterial growth (3,4,5).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the aqueous and methanol extract of miswak has biochemical activity against organisms involved in the pathogenesis of DP [4]. Palombo [5] and Omer et al [6] have also reported that methanolic extract of S. persica reduces adhesion of microbial pathogens to the tooth surface, which is a main event in the formation of DP and the progression to tooth decay and periodontal diseases.…”
Section: Introductionmentioning
confidence: 99%